The Effect of Service Quality on Customer Satisfaction (A Study at Mitra Baru Gold Shop Sampit) - Sari Atul Hilaliyah (Universitas Darwan Ali, 2025)
This study aims to examine the extent to which service quality affects customer satisfaction, with price considered as an influencing factor. The research focuses on Toko Emas Mitra Baru 1 in Sampit City, due to the increasingly intense competition in the gold jewelry sector, which requires companies to offer better services as a way to differentiate themselves. The study employs a quantitative approach, collecting data from 73 individuals who have conducted transactions at the store, selected through purposive sampling. The results indicate that service quality has a positive and significant impact on customer satisfaction. This finding suggests that the better the service quality, the higher the customer satisfaction. On the other hand, price does not show a significant effect, implying that customers pay more attention to the service experience, comfort, and sense of security during transactions rather than relatively small differences in price. These results support the argument that, in the gold business, service quality is a crucial factor in maintaining customer loyalty and building competitive advantage.